Pengaruh Role Ambiguity, Role Conflict, dan Role Overload terhadap Kinerja Pegawai Dimediasi Perilaku Cyber-loafing - Ahmad Ahmad; Dian A.S. Parawansa; Jusni - (Hasanuddin Journal of Business Strategy, 2019)
Internet usage activities Cyberloafing is related to hobbies or transfer employees Burnout or stress ofworking with a variety of entertainment that existed on diinternet working hours.This research aims toknow the influence of Role Ambiguity, Role Conflict and Role Overload on performance Clerk MediatedBehavior Cyberloafing on Bureau of academic and General University of West Sulawesi. This researchapproach is the quantitative approach. The population in this study was a clerk in the Bureau ofacademic and General University of West Sulawesi. The source of the data used in this study i.e., primarydata and secondary data. Data collection techniques applied is questionnaire and documentation. Dataprocessing and analysis is carried out using the program SPSS (Statistical Product and Service Solution)version 25.0. As for the analysis is the analysis of the path (Path Analysis). The results of this studysuggest that (1) there is a significant positive influence and role ambiguity, role conflict, and roleoverload, cyberloafing behaviour towards employees. (2) There is a significant negative influence androle ambiguity, role conflict, role overload, cyberloafing on performance and employees. (3) there is asignificant negative influence and role ambiguity, role conflict and role overload, on performance clerkmediated cyberloafing behavior